The clopidogrel story: a cautionary tale of pharmacogenomics and personalized medicine - Iqbal, Waheed (International Journal of Pathology, 2025)
Clopidogrel, a widely used antiplatelet drug, has been a cornerstone in the prevention of cardiovascular events in patients with atherosclerotic vascular disease. Clopidogrel works by inhibiting adenine diphosphate (ADP) induce platelet aggregation by binding to P2Y12 receptor. However, the story of clopidogrel serves as a cautionary tale in the era of pharmacogenomics and personalized medicine. The discovery of genetic variations in the CYP2C19 and P2Y12 that affect clopidogrel metabolism and efficacy, has significant implications for patient care.